How can food environments support greater fruit and vegetable consumption in Tanzania? A multi-stakeholder workshop to share findings and co-develop recommendations for interventions in Arusha Region - de Bruyn, Julia; Msangi, Sheila; Mukasa, Lydia; Gordon, Jessica (CGIAR System Organization, 2024)
The workshop described in this report follows an initial collaborative needs assessment workshop conducted in March 2024, which brought together diverse food systems stakeholders to identify challenges and opportunities relating to the various dimensions of the food environment (Turner et al., 2018): fruit and vegetable availability, prices, product and vendor properties, marketing and regulations. An overview of ideas emerging from this first workshop are included in Annex 1. Both workshops have been co-hosted with the Arusha Sustainable Food Systems Platform, a multistakeholder group led by Rikolto and a key partner of the FRESH Initiative.